THE INFLUENCE OF CURRENT RATIO, DEBT TO ASSET RATIO AND TOTAL ASSET TURNOVER ON PROFIT CHANGES AT PT. UNILEVER TBK PERIOD 2014-2021 - Nurilmi Awalia; Abdi Akbar; Nurman; Anwar; Andi Mustika Amin (Transpublika Publisher, 2023)
This study examines the impact of the Current Ratio, Debt to Asset Ratio, and Total Asset Turnover variables on earnings changes at PT. Unilever Tbk for the period of 2014-2021. The study utilizes secondary data from 32 samples. The analysis involves descriptive analysis, classical assumption tests, multiple linear regression, and hypothesis testing. The findings indicate that the Debt to Asset Ratio variable has no significant partial effect, whereas the Current Ratio and Total Asset Turnover exhibit a significant impact on earnings changes. However, the F test reveals that when considered together, the Current Ratio, Debt to Asset Ratio, and Total Asset Turnover do not have a significant effect on earnings changes. The analysis demonstrates that the Debt to Asset Ratio has no significant impact on changes in earnings, contradicting (H2), which suggests a positive and significant relationship between the two. Conversely, Total Asset Turnover demonstrates a positive and significant effect on earnings changes, supporting (H3) which states a partial and significant influence. Simultaneously, the Current Ratio, Debt to Asset Ratio, and Total Asset Turnover do not significantly affect earnings changes, contrary to (H4) which assumes a significant combined effect. Overall, the results indicate that the Current Ratio partially influences earnings changes, while the Debt to Asset Ratio and Total Asset Turnover do not significantly affect them.